Some aspects of terpenoid chemistry - Weston, R; Weston, Roderick James (1971)
﻿ The chemotaxonomy and the biosynthesis of tetranortriterpenes is briefly reviewed in chapter one and the partial syntheses of some of these products is described. The work described in the first part of chapter two was directed towards a synthesis of the andgamma;-lactone ring system in the side chain of flindissol, while that in the latter part involved studies of the allylic oxidation in ring D of some apotirucallol derivatives. The acid constituents of Manila elemi resin were separated and methyl 3andalpha;-acetoxytirucalla-8,24-dien-21-oate (1) was then converted to 3andbeta;-acetoxytirucall-8,24-dien-21-oic acid. Bromination of this acid resulted in low yields of the dibromide and an explanation for this was put forward. The action of ammonia on the acyl chloride of 3andalpha;-acetoxytirucalla-8,24-dien-21-oic acid followed by reaction with lead tetra-acetate and iodine led to formation of 3andalpha;-acetoxy(21-24)cyclotirucalla-7,9(11),24-trien-21-one. Reaction of 3andalpha;-acetoxytirucall-8-en-21-amide with lead tetra-acetate and iodine resulted in formation of 3andalpha;-acetoxytirucalla-7,9(11)-dien-21-isocyanate and explanations for these results are given. Ozonolysis was used extensively during this work and the mechanism of ozonolysis is discussed. Treatment of a mixture of methyl 3andalpha;-acetoxytirucall-7 and 8-en-21-oate with ozone gave three products, methyl 3andalpha;-acetoxy-7andalpha;,8andalpha;-epoxytirucallan-21-oate (2), methyl 3andalpha;-acetoxy-7-oxotirucall-8-en-21-oate and methyl 3andalpha;-acetoxy-7,11-dioxotirucall-8-en-21-oate. The 7andalpha;,8andalpha;-epoxide (2) was rearranged with boron trifluoride and acetylation of the product gave methyl 3andalpha;,7andalpha;-diacetoxyapotirucall-14-en-21-oate (3). A crude mixture of dibromo elemi acid methyl esters was ozonised and reductive work up gave four products, (13andalpha;H)ursan-3,12-dione, methyl 3,7-dioxotirucalla-8,24-dien-21-oate, methyl 3,7, 11-trioxotirucalla-8,24-dien-21-oate and methyl 7andalpha;-bromo-3,15-dioxo-(14andalpha;H)apotirucall-24-en-21-oate (4). Similarly ozonolysis of a crude mixture of methyl 3andalpha;-acetoxy-24,25-dibromo-tirucall-7 and 8-en-21-oate and reductive work up gave a mixture of seven products. Methyl 3andbeta;-acetoxy-12-oxo-(13andbeta;H)ursan-28-oate, methyl 3andalpha;-acetoxy-7andalpha;,8andalpha;-epoxytirucall-24-en-21-oate (5), methyl 3andalpha;-acetoxy-7andalpha;-bromo-15-oxo-(14andalpha;H)apotirucall-24-en-21-oate (6), methyl 3andbeta;-acetoxy-11-oxours-12-en-28-oate (7), methyl 3andalpha;-acetoxy-7,11-dioxotirucalla-8,24-dien-21-oate, methyl 3andalpha;-acetoxy-7-oxotirucalla-8,24-dien-21-oate and methyl 3andalpha;-acetoxy-14andbeta;,15andbeta;-epoxy-7andalpha;-hydroxyapotirucall-24-en-21-oate (8). The structure and mechanism of formation of (7) and (8) is discussed. The crude 7andalpha;,8andalpha;-epoxide (5) was rearranged with boron trifluoride and acetylation of the product gave methyl 3andalpha;,7andalpha;-diacetoxyapotirucalla-14,24-dien-21-oate (9). The structure and mechanism of formation of the two 7andalpha;-bromides (4) and (6) is discussed. Reaction of methyl 3andalpha;-acetoxy-24,25-dibromotirucall-8-en-21-oate with tetramethylammonium acetate gave methyl 3andalpha;-acetoxy-24-bromotirucalla-8,24-dien-21-oate which was reduced to 24-bromotirucalla-8,24-dien-3andalpha;,21-diol and reduction of this diol gave tirucall-8-en-3andalpha;,21-diol. Oxidation of (1) with iodine and iodic acid in aqueous dioxan and acetylation of the products gave methyl 3andalpha;-acetoxy-24andxi;,25-epoxytirucall-8-en-21-oate and methyl 3andalpha;,24andxi;-diacetoxy-25-hydroxytirucall-8-en-21-oate which was hydrolysed to methyl 3andalpha;,24,25-trihydroxytirucall-8-en-21-oate. Bromination of (9) gave methyl 3andalpha;,7andalpha;-diacetoxy-24,25-dibromoapotirucall-14-en-21-oate (10) in 38% yield. Oxidation of this dibromide with selenium dioxide gave what is thought to be the 14,15-diol and the mechanism of oxidation with selenium dioxide is discussed. Treatment of (3) with bispyridinechromium oxide and also with aqueous N-bromosuccinimide gave methyl 3andalpha;,7andalpha;-diacetoxy-16-oxoapotirucall-14-en-21-oate in good yield. Similarly oxidation of (10) with bispyridinechromium oxide gave the 14-en-16-one in good yield but after denomination, methyl 3andalpha;,7andalpha;-diacetoxy-16-oxoapotirucall-14,24-dien-21-oate decomposed on attempted purification. Deoxygenation of havanensin triacetate with a zinc-copper couple deoxyhavanensin triacetate in good yield but attempts to oxidise this alkene with either selenium dioxide or bispyridinechromium oxide were unsuccessful. Oxidation of this alkene with aqueous chromic acid gave isophotodeoxyhavanensin triacetate. The literature of the chemistry of some pentacyclic triterpene-12-ketones is discussed in chapter three together with the structures of some new 12-ones and their o.r.d. curves and mass spectra. The triterpene lupeol was used as a model system to construct the 1andalpha;,3andalpha;-diacerate group common to the meliacins and this work is described in chapter four. Lupeol benzoate was firstly converted to lupan-3-one. Treatment of lupan-3-one hydrazone with lead tetra-acetate gave 5(4andrarr;3)-abeolup-3-ene and the mechanism of this reaction is discussed. Bromination of lupan-3-one gave a mixture of 2(andalpha; and andbeta;)-bromolupan-3-ones which was dehydrobrominated to lup-1-en-3-one. Epoxidation of this enone with hydrogen peroxide gave 1andalpha;,2andalpha;-epoxylupan-3-one which on rearrangement with hydrazine gave lup-2-en-1andalpha;-ol. Epoxidation of this alcohol gave 2andalpha;,3andalpha;-epoxylupan-1andalpha;-ol which was reduced with lithium in ethylamine to lupan-1andalpha;,3andalpha;-diol. The yield of this diol was greater by this route than by reduction of 1andalpha;,2andalpha;-epoxylupan-3-one. The o.r.d. of some lupan-3-ones is also discussed. The structure of a new diterpene furan and an attempt to synthesise this product from sclareol is described in chapter five. Oxidation of sclareol with chromic acid in acetic acid gave norambreinolide and 8andalpha;-acetoxy-13,14,15,16-tetranorlabdan-12-oic acid. Methanolysis of norambreinolide gave a 1:1 mixture of starting material and methyl 8andalpha;-hydroxy-13,14,15,16-tetranorlabdan-12-oate and a synthetic route via this ester was not pursued. Reduction of norambreinolide gave 13,14,15,16-tetranorlabdan-8andalpha;,12-diol which gave 8andalpha;-acetoxy-13,14,15,16-tetranorlabdan-12-yl acetate on acetylation. Dehydration of this acetate with phosphoryl chloride gave a mixture of 13,14,15,16-tetranorlabd-7 and 8(17)-en-12-yl acetates. Hydrolysis of this mixture and oxidation of the alcohols with silver carbonate gave a mixture of 13,14,15,16-tetranorlabd-7 and 8(17)-en-12-als. Reformatsky condensation of these aldehydes with ethyl andalpha;-bromoacetate gave a mixture of ethyl 12-hydroxy-15,16-dinorlabd-7 and 8(17)-en-14-oates. Treatment of this mixture of hydroxyesters with o-monoperphthalic acid gave pure ethyl 12andxi;-hydroxy-15,16-dinorlabd-8(17)-en-14-oate, together with ethyl 7andalpha;, 8andalpha;-epoxy-12andxi;-hydroxy-15,16-dinorlabdan-14-oate. The C-12 epimers of these products were separated and their spectra and the configuration of these epimers at C-12 is discussed. Oxidation of ethyl 12andxi;-hydroxy-15,16-dinorlabd-8(17)-en-14-oate gave ethyl 12-oxo-15,16-dinorlabd-8(17)-en-14-oate. Reaction of this andbeta;-keto-ester with 1,2-dichloroethyl ethyl ether and aqueous sodium hydroxide gave only traces of a furan while in triethylamine, a mixture of products was obtained. From these results it was concluded that a different approach to synthesis of the furan ring may be necessary.